Cycling and walking for transport and their associations with diabetes and risk factors for cardiovascular disease. (December 2018) - Riiser, Amund; Solbraa, Ane; Jenum, Anne Karen; Birkeland, Kåre I.; Andersen, Lars Bo
Abstract: Introduction: Active travel is recommended and promoted to increase physical activity and reduce the risk of several non-communicable diseases. The health effects of active travel in populations of low socioeconomic status (SES) are unclear. This study was performed to investigate the associations of cycling and walking for travel with diabetes and other risk factors for cardiovascular disease (CVD) in a multi-ethnic, low-SES population. Methods: Cross-sectional data from 2445 adults (age, 48.0 ± 9.8 years; 43.6% men) in two multi-ethnic, low-SES districts in Oslo, Norway, were collected. The data included objective measurements (blood pressure, weight, height, blood parameters), questionnaire data (physical activity, diabetes, use of medication, working status, education, smoking), sex, age, and country of origin. Associations were analyzed by multiple logistic regression models. Results: Cycling and walking for travel were performed by 26.5% and 80.1% of adults, respectively. Self-reported diabetes (OR, 0.47; 95% CI 0.23–0.94) high-density lipoprotein cholesterol level of <1.3 mmol/L (OR, 0.77; 95% CI, 0.62–0.95) and obesity (OR, 0.71; 95% CI, 0.55–0.92) were inversely associated with cycling after adjustment for SES, smoking, leisure-time physical activity, walking for travel, age, and sex. Systolic blood pressure of >140 mmHg (OR, 0.74; 95% CI, 0.57–0.97) was inversely associated with walking for travel. Conclusion: In the current multi-ethnic low SES population, those engaged in active travel and cycling for travel in particular had lower odds of diabetes and lower risk factors for cardiovascular disease compared to those not engaged in active travel. Highlights: Active travelers in communities with low SES have better cardiovascular risk profile and less diabetes. Those cycling for transport have less diabetes and more beneficial levels of HDL. Those walking for transport have lower blood pressure. Active travel in general and cycling in particular should be facilitated in communities with low SES.